Periconceptional undernutrition increases quantity and quality of oocyte population, but not cognitive or emotional response of 60‐day‐old lambs. Issue 3 (21st June 2014) - Abecia, J. A.; Casao, A.; Pascual‐Alonso, M.; Lobón, S.; Aguayo‐Ulloa, L. A.; Forcada, F.; Meikle, A.; Sosa, C.; Marín, R. H.; Silva, M. A.; Maria, G. A.
Summary: Maternal periconceptional undernutrition is associated with altered development and increased risks of adverse outcomes in the offspring. The aim of this work was to determine the effect of periconceptional undernutrition on behavioural and reproductive aspects of the offspring. Fifty ewes were synchronized in oestrus (day 0) and allocated to two groups ( n  = 25) to be fed diets that provided 1.5 (C) or 0.5 (L) times the requirements for maintenance until day 15. Ewes were mated and fed the control diet from day 16 until lambing. Two months after lambing, 26 lambs were exposed to tests to determine their cognitive/emotional responses. Six ewe lambs were euthanized and in vitro oocyte maturation and fertilization procedures performed. The experimental diets produced no changes of mean live weight (LW) of C ewes, L ewes presenting a reduction in their initial LW with significant differences at day 15, in comparison with C ewes (p < 0.05). L ewes experienced a significant reduction in their body condition (BC) in comparison with C ewes (p < 0.05). Fourteen days after the onset of the experimental diets, mean LW and BC of L ewes was significantly lower than those of C ewes (p < 0.05). Undernourished ewes presented a trend to a reduction of prolificacy and fecundity (p < 0.10) in comparison with C ewes. Emotional and cognitive test revealed a similar response between groups. Ewe lambs from the undernourished ewes presented a population of oocytes 1.7 times higher than ovaries from control ewe lambs (66.0 ± 0.73 vs. 113.7 ± 15.6 oocytes; p < 0.05) and had more oocytes in the 'good' (p < 0.05) and 'healthy' (p < 0.05) categories. In conclusion, a low plane of nutrition around conception significantly increases quantity and quality of the oocyte population of 60‐day‐old female descendants. Modifications of the cognitive and emotional responses of the progeny have not been evidenced.